Ing4-deficiency promotes a quiescent yet transcriptionally poised state in hematopoietic stem cells - Zanshé Thompson; Georgina A. Anderson; Marco Hernandez; Carlos Alfaro Quinde; Alissa Marchione; Melanie Rodriguez; Seth Gabriel; Vera Binder; Alison M. Taylor; Katie L. Kathrein (iScience, 2024)
Summary: Defining the mechanisms that regulate stem cell maintenance, proliferation, and differentiation is critical for identifying therapies for improving stem cell function under stress. Here, we have identified the tumor suppressor, inhibitor of growth 4 (Ing4), as a critical regulator of hematopoietic stem cell (HSC) homeostasis. Cancer cell line models with Ing4 deficiency have shown that Ing4 functions as a tumor suppressor, in part, due to Ing4-mediated regulation of several major signaling pathways, including c-Myc. In HSCs, we show Ing4 deficiency promotes gene expression signatures associated with activation, yet HSCs are arrested in G0, expressing several markers of quiescence. Functionally, Ing4-deficient HSCs demonstrate robust regenerative capacity following transplantation. Our findings suggest Ing4 deficiency promotes a poised state in HSCs, where they appear transcriptionally primed for activation but remain in a resting state. Our model provides key tools for further identification and characterization of pathways that control quiescence and self-renewal in HSCs.